2014
DOI: 10.12944/cwe.9.3.27
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Sequestration Potential of Teak Plantations of Different Agro-Climatic Zones and Age-Gradations of Southern India

Abstract: Carbon sequestration potential of teak plantations in different agro-climatic zones of Southern India, viz. Northern Dry Zone, Northern Transition Zone, and Hilly Zone were studied. Teak plantations belonging to three age gradations viz. 10, 15 and 20 years were considered for the study. Above ground biomass was computed based on volume estimation and wood density after considering three 10 x 10 m plots. Carbon sequestration potential of teak plantations on farmlands differed significantly with respect to agro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
0
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
1
0
0
Order By: Relevance
“…(65.78 t/ha) which could be attributed to maximum total biomass production and growth habit recorded in tree species (Table 3). These results are in accordance with Swamy (2010), reported in different shelterbelt trees at different time interval and also in line with Reddy et al, (2014).…”
Section: Resultssupporting
confidence: 93%
“…(65.78 t/ha) which could be attributed to maximum total biomass production and growth habit recorded in tree species (Table 3). These results are in accordance with Swamy (2010), reported in different shelterbelt trees at different time interval and also in line with Reddy et al, (2014).…”
Section: Resultssupporting
confidence: 93%
“…This suggests that the age of teak trees significantly influences their capacity to sequester carbon which indicates that older trees tend to accumulate more carbon (Kraenzel et al 2003;Wirabuana et al 2022). This agrees with the findings of Chanan and Iriany (2014) in Indonesia, Reddy et al (2014) in Southern India, and Chayaporn et al (2021) in Thailand.…”
Section: Tree Carbon Content and Carbon Dioxide Equivalent In The Dif...supporting
confidence: 92%
“…Further, the carbon sequestration of the trees under high RFZ was higher than that of low RFZ. The research by Reddy et al [24] on the above-ground biomass of teak plantations on farmlands showed substantial differences concerning agro-climatic zones and age, which supported these findings. At all three age gradations, teak plantations grown on farmlands in the Northern Transition Zone had considerably higher above-ground biomass than those in the Northern Dry Zone and Hilly Zone.…”
Section: Resultsmentioning
confidence: 61%